Comparison of Extraction Variations on Mitragynine Level of Three Variants of Kratom Leaves (Mitragyna speciosa Korth) - Mutiara, Syrifah Nur Intan; Masriani, Masriani; Muharini, Rini; Sapar, Ajuk; Rasmawan, Rahmat (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Kratom leaves are known as traditional medicine with various benefits, such as antibacterial, antimicrobial, and antioxidant properties. These benefits are attributed to the presence of secondary metabolites, particularly mitragynine. Mitragynine can be obtained through extraction methods. However, to date, no research has compared the efficiency of sonication, reflux, and soxhletation extraction methods on three variants of kratom leaves for obtaining mitragynine. This study aimed to compare the effectiveness of the extraction methods by extracting 15 grams of three variants of kratom leaves using the sonication, reflux, and soxhlet methods. Each extract obtained was quantitatively analyzed using a UV- Vis spectrophotometer to determine the amount of alkaloid and HPLC to determine the amount of mitragynine. The results indicate that the most efficient method for obtaining total alkaloid from the green variant (19.125 mg/g) is through sonication and reflux, the red variant (31,625 mg/g) and the white variant (26,125 mg/g) are through sonication. The most efficient method for obtaining mitragynine from green (22.21 mg/g) is sonication, from red (29.15 mg/g) is reflux, and from white (24.62 mg/g) is soxhletation. Overall, these data show that different extraction methods produce different levels of mitragynine in each kratom variant.